New aminoacyl-tRNA synthetase-like protein in insecta with an essential mitochondrial function. - Guitart, T.; Leon Bernardo, T.; Sagalés, J.; Stratmann, T.; Bernués, J.; Ribas de Pouplana, L. (Journal of Biological Chemistry, 2010)
Aminoacyl-tRNA synthetases (ARS) are modular enzymes that aminoacylate transfer RNAs (tRNA) for their use by the ribosome during protein synthesis. ARS are essential and universal components of the genetic code that were almost completely established before the appearance of the last common ancestor of all living species. This long evolutionary history explains the growing number of functions being discovered for ARS, and for ARS homologues, beyond their canonical role in gene translation. Here we present a previously uncharacterized paralogue of seryl-tRNA synthetase named SLIMP (seryl-tRNA synthetase-like insect mitochondrial protein). SLIMP is the result of a duplication of a mitochondrial seryl-tRNA synthetase (SRS) gene that took place in early metazoans and was fixed in Insecta. Here we show that SLIMP is localized in the mitochondria, where it carries out an essential function that is unrelated to the aminoacylation of tRNA. The knockdown of SLIMP by RNA interference (RNAi) causes a decrease in respiration capacity and an increase in mitochondrial mass in the form of aberrant mitochondria.